Extension on the Tibetan plateau: recent normal faulting measured by InSAR and body wave seismology - Elliott, J; Walters, R; England, P; Jackson, J; Li, Z; Parsons, B (2010)
We use InSAR and body wave modelling to determine the faulting parameters for a series of five Mw 5.9-7.1 normal faulting earthquakes that occurred during 2008, including the March 20 Yutian earthquake (Mw 7.1), one of the largest normal faulting events to have occurred recently on the continents. We also study three earlier normal faulting earthquakes that occurred in southern Tibet between 1992 and 2005. Coseismic deformation for each of these eight events is measured with ascending and descending interferograms from ENVISAT, ERS and ALOS SAR data. Elastic dislocation modelling of the line-of-sight InSAR displacements and body wave seismological modelling of P and SH waves are used to estimate fault parameters and are found to be in good agreement for all the events studied. The use of InSAR to measure deformation allows a relatively precise determination of the fault location in addition to resolving the focal plane ambiguity. Only five of the eight events are associated with a clear surface topographic feature, suggesting that an underestimation of the amount of extension would result from using the surface expressions of normal faulting alone. The observations, in all cases, are consistent with slip on planar surfaces, with dips in the range 40-50°, that penetrates the uppermost crust to a depth of 10-15 km. We find no evidence for active low-angle (dip less than 30°) normal faulting. The contribution of the normal faulting to overall extension estimated by summing seismic moments over earthquakes for the past 43 yr is 3-4 mm yr-1, or 15-20 per cent of the rates of extension measured across the plateau using GPS. 85 per cent of the moment release in normal faulting over the past 43 yr has occurred in regions whose surface height exceeds 5 km. This observation adds weight to the suggestions that the widespread normal faulting on the plateau is the result of variations in the gravitational potential energy of the lithosphere. © 2010 The Authors Geophysical Journal International © 2010 RAS.